Covidex: an ultrafast and accurate tool for virus subtyping - Cacciabue, Marco Polo Domingo (2020)
Covidex is an open-source, alignment-free machine learning subtyping tool for viral species. It is a shiny app that allows a fast and accurate classification in pre-defined clusters for SARS-CoV-2 and FMDV genome sequences. The user can also build its own classification models with the Covidex model generator.